1991
DOI: 10.1111/j.1699-0463.1991.tb05170.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of lipofuscinogenesis: Effect of the inhibition of lysosomal proteinases and lipases under varying concentrations of ambient oxygen in cultured rat neonatal myocardial cells

Abstract: U . T. Mechanisms of lipofuscinogenesis: Effect of the inhibition of lysosomal proteinases and lipases under varying concentrations of ambient oxygen in cultured rat neonatal myocardial cells. APMIS 99: 41M26, 1991.The objective of this study was to analyse the relative roles of oxidative stress and lysosomal lytic enzymes in lipofuscin formation in cultured neonatal rat cardiac myocytes. Myocytes were exposed to E-64 (an inhibitor of lysosomal cathepsins L, D and H), netilmicin (an inhibitor of lysosomal phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 38 publications
3
12
0
1
Order By: Relevance
“…This hypothesis is in agreement with the results of biochemical observations showing that orthophosphates and pyrophosphates are strong inhibitors of the lysosomal enzyme activity of earthworm chloragocytes (Varute and More 1973). It has been found that both inhibition of lysosomal hydrolases and oxidative stress play a significant role in lipofuscinogenesis (Marzabadi et al 1991).…”
Section: Discussionsupporting
confidence: 91%
“…This hypothesis is in agreement with the results of biochemical observations showing that orthophosphates and pyrophosphates are strong inhibitors of the lysosomal enzyme activity of earthworm chloragocytes (Varute and More 1973). It has been found that both inhibition of lysosomal hydrolases and oxidative stress play a significant role in lipofuscinogenesis (Marzabadi et al 1991).…”
Section: Discussionsupporting
confidence: 91%
“…The accumulation of lipofuscin-like autofluorescent materials in NG108-15 cells was accelerated by the thiolprotease inhibitors E-64 and leupeptin, as reported previously for rat neurons [6] and cultured cardiac myocytes [7]. These results indicate that a decrease of the proteolytic activities during neuronal differentiation causes the formation of the materials in NG108-15 cells and suggest that some components in the materials must be peptidic substances.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, it was reported that the activity of cathepsin B, which is the major lysosomal thiolprotease in rat brain [30,31], was not decreased with age [32]. Therefore, these 7 results also support the above-mentioned concept that an imbalance of proteolysis plays a part in lipofuscin formation in the rat neuron.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations